PERENCANAAN EVAPORATOR PADA FREEZER DENGAN KAPASITAS 8 KG - Sugeng Hariyadi; Iwan Riswanto (Wahana Teknik, 2012)
Food storage to avoid damage requires a proper treatment. One way of food storage is to cool the food is below freezing point. The role of cooling techniques is essential to achieving that goal.Freezer is one of the tools that are often used for the storage of foodstuffs. The main components of the freezer is the compressor, condenser, evaporator and expansion equipmentRefrigeration system consists of supporting components in a refrigeration system planning capacity of 8 kg of this product includes planning detail is only one principal component of the evaporator which is focused only on technical aspects in which the calculation is based on the principles of thermodynamics and heat transfer. This plan is intended to determine the dimensions of the evaporator or vaporizer equipment in accordance with the refrigeration capacity of 8 kg of product.Keywords : planning, evaporator, freezer